Politik Hukum Pengaturan Plea Bargaining Dalam Penegakan Hukum Perkara Pidana Di Indonesia - Arky, Arky; Indra, Mexsasai; Diana, Ledy (Jurnal Ilmiah Wahana Pendidikan, 2024)
In Law Number 48 of 2009 concerning Judicial Power, it is stated that justice must be based on simplicity, speed and low costs. However, in reality the process of trying in court in Indonesia is very inversely proportional, considering the large number of cases that have to be resolved at a very high cost, very long queues and the buildup of cases in Indonesian courts which is increasing. This research will understand the concept of plea bargaining which will be added to the criminal justice system in Indonesia. This type of research can be classified as normative juridical research, because this research is carried out by examining secondary data and approaches to law. This normative research examines the applicable regulations and links them with legal politics in the formation of rules to achieve the ideal concept in implementation of Plea Bargainig. The results of this research examine and analyze the rules relating to plea bargaining in the United States and several other countries to obtain the urgency and ideal concept for implementing plea bargaining in Indonesia. The fundamental element for the author to research is Law Number 48 of 2009 Article 2 paragraph (4) concerning judicial power considering that this law contains the principles of justice which is carried out quickly, simply and at low cost. So this is very much in conflict with the reality that exists in the court process in Indonesia.